Peningkatan penerimaan diri pasien skizofrenia melalui Rational Emotif Behavior Therapy - Aldila Putri Karindra (Universitas Muhammadiyah Malang, 2021)
Delusions and irrational thoughts often appear in schizophrenic patients. Can those negative thoughts be reduced to them? Rational Emotive Behavior Therapy (REBT) is designed to help overcome the problems of negative thinking in schizophrenia. The assessment was carried out using interviews, observation and several psychological tests with the results of the dominance of negative feelings and low self-acceptance. The intervention aims to break irrational beliefs and increase self-acceptance through REBT techniques. The results of the intervention show that the client can see things from a different perspective in order to generate new, more rational thoughts so as to increase the client’s acceptance of himself, others, and the environment.